RESOURCE-SAVING PROCESS AND RESOURCE-SAVING TECHNOLOGIES IN THE FIELD OF ECOLOGICAL TOURISM - Nikolaiev, K. D.; Isaienko, V. M.; Zelenko, Yu. V. (Science and Transport Progress, 2009)
Saving of resources and some resources-saving technologies, the use of which in eco-touristic sphere will bring the possibility of development with the least pressure upon the environment, are considered in this article.